2020
DOI: 10.1002/dmrr.3384
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically stable analogue of the gut‐derived peptide xenin on beta‐cell transdifferentiation in high fat fed and insulin‐deficient Ins1Cre/+;Rosa26‐eYFP mice

Abstract: Background The antidiabetic effects of the gut hormone xenin include augmenting insulin secretion and positively affecting pancreatic islet architecture. Methods The current study has further probed pancreatic effects through sub‐chronic administration of the long‐acting xenin analogue, xenin‐25[Lys13PAL], in both high fat fed (HFF) and streptozotocin (STZ)‐induced insulin‐deficient Ins1Cre/+;Rosa26‐eYFP transgenic mice. Parallel effects on metabolic control and pancreatic islet morphology, including islet bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In relation to this, there was a reduction in islet‐ and beta‐cell areas, as well as pancreatic insulin content, in both treatment groups of HFF mice, accompanied by decreased proliferation of both alpha and beta cells. Thus, changes in islet‐cell proliferation rates, or in recently reported islet cell transitioning events, 44 probably outweigh decreased beta‐cell apoptosis observed with both peptides. Moreover, GLP‐1 receptor signalling has recently been linked to positive effects on alpha‐ and beta‐cell transdifferentiation 45 .…”
Section: Discussionmentioning
confidence: 80%
“…In relation to this, there was a reduction in islet‐ and beta‐cell areas, as well as pancreatic insulin content, in both treatment groups of HFF mice, accompanied by decreased proliferation of both alpha and beta cells. Thus, changes in islet‐cell proliferation rates, or in recently reported islet cell transitioning events, 44 probably outweigh decreased beta‐cell apoptosis observed with both peptides. Moreover, GLP‐1 receptor signalling has recently been linked to positive effects on alpha‐ and beta‐cell transdifferentiation 45 .…”
Section: Discussionmentioning
confidence: 80%
“… 76 Remarkably, the same study also demonstrated long-acting positive metabolic effects of (DAla 2 )GIP/xenin-8-Gln following 14-day cessation of treatment. 76 This could suggest positive metabolic reprogramming induced by co-activation of GIP and xenin receptor pathways in keeping with positive effects on beta cell function and integrity, 6 , 29 , 43 and represents a potential benefit for future antidiabetic therapy. Such observations are extremely important moving towards the clinical setting given the complex aetiology and progressive nature of type 2 diabetes mellitus in humans.…”
Section: Dual and Triple Acting Therapeutic Approaches That Incorporate Xenin Elementsmentioning
confidence: 96%
“… 27 However, effects of xenin independent of neurotensin receptor activation have been demonstrated, 28 highlighting the need for further detailed studies in this area. Finally, although there is no direct evidence for xenin induced benefits in type 1 diabetes mellitus, reduction of beta-cell apoptosis 10 alongside positive actions on islet cell transdifferentiation, 29 could be suggestive of positive effects of xenin in this disease state.…”
Section: Function Potential Mechanism Of Action and Therapeutic Application Of Xeninmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, we used transgenic mice with beta-cell lineage tracing capabilities, to investigate the impact of transdifferentiation of beta- to alpha-cells in Ac3IV-induced improvements of pancreatic islet architecture in diabetes. Fully characterised transgenic Ins1 Cre/+ ; Rosa26-eYFP mice were utilised [ 10 , 11 , 13 , 14 , 16 ], alongside induction of diabetes and islet damage by multiple low dose streptozotocin (STZ) administration. The subsequent impact of 12 days pharmacological upregulation of V1a and V1b receptor pathways by Ac3IV on beta-cell lineage was then studied.…”
Section: Introductionmentioning
confidence: 99%